2013
DOI: 10.1007/s10854-013-1524-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of flat textile material as inhomegeneous and anisotropic structure

Abstract: The main purpose of the study was to present the basic problems of determining surface resistance of electroconductive fabric. The attention was paid to the arrangement of electrodes on a sample. Analysis of the contact resistance between the measuring electrode and the fibrous substrate was conducted. The multi-variant research of a textile sample has shown that the electrodes arrangement is of significance for sample resistance measurement results. The arrangement of four electrodes on the edge of the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Moreover, measuring surface resistance of flat shape textile samples is difficult because of current flowing into the shape cannot be isolated only in the surface, but a part of it can penetrate through the volume. Numerous methods and standards can be found in literature [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For example, two and four probe electrical resistance measurement methods, where the most accurate and widely used methods are four probe placements.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, measuring surface resistance of flat shape textile samples is difficult because of current flowing into the shape cannot be isolated only in the surface, but a part of it can penetrate through the volume. Numerous methods and standards can be found in literature [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For example, two and four probe electrical resistance measurement methods, where the most accurate and widely used methods are four probe placements.…”
Section: Introductionmentioning
confidence: 99%
“…Electroconductive properties of woven and knitted fabrics are modeled using the equivalent resistance schemes in particular. [12][13][14][15][16] The fabric is seen from an electrical point of view as an electrical circuit composed of connected resistors and a battery. Yarns are ideal resistors of known resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that electrodes should not be too close to the edge of the sample that the error will not be introduced [3,15]. To avoid this, additional measurements need to be performed.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid this, additional measurements need to be performed. A table with four holes drilled was prepared allowing the electrodes to fall freely under their weight onto the textile material [15]. This table allowed electrodes to be arranged in the shape of a square with side of 20 mm, 40 mm and 60 mm (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation